SATELLITE ATTITUDE CONTROL SYSTEM DESIGN WITH NONLINEAR DYNAMICS AND KINEMTICS OF QUATERNION USING REACTION WHEELS (Revista Interdisciplinar de Pesquisa em Engenharia, 2017)
The success of a space mission where the satellite must perform rapid attitude maneuvers with great angles is extremely dependent of a careful investigation of the nonlinear dynamics of the satellite. Since these big maneuvers imply in the dynamic coupling between the satellites angular motion and the actuators such as reaction wheels and/or gas jets. As a result, this coupling must be taking into account in the Attitude Control System (ACS) design. This paper presents the nonlinear model derivation of a rigid satellite and the performance comparison of two controllers designed by Lyapunov and LQR methods. Thedynamics of the satellite is initially derived in the non-linear Euler equations form and the kinematics is based on the quaternion parametrization which represent the rotation and attitude motion, respectively. In the sequel, the linear model is obtained where linearization is about an operating point of the arbitrary angular velocity and the reaction wheel angular momentum. From this model, several simulations are performed in order to investigate the influence of the nonlinear dynamics in the in the SCA performance which is designed by trial and error and by the Linear Quadratic Regulator approaches. The ACS performance is evaluated considering the capacity of the reaction wheels to maintain the stability and to control the angular velocity and the attitude of the satellite. The stability is investigated comparing the location of the poles and zeros of the open and closed loops. The ACS performance is evaluated comparing the amount of energy spend by each control law. Keywords: Satellite Control, nonlinear dynamics, LQR and Lyapunov theory